Research on Microstructure Evolution of Deposited Metal of Low Nickel High Nitrogen Austenitic Stainless Steel - Yiming Ma; Xiaochun Lv; Naiwen Fang; Kai Xu; Xingxing Wang; Yicheng Yang; Hongliang An; Yan Zhang; Yinan Xu (Advances in Materials Science and Engineering)
In this paper, in situ observation of the cooling process of the deposited metal of low nickel high nitrogen austenitic stainless steel obtained by laser-arc hybrid surfacing welding with shielding gas containing only Ar and only N2, respectively, is carried out using the ultra-high-temperature confocal laser scanning microscope (CLSM). An in-depth analysis of the microstructural changes is conducted with SEM, EDS, and EBSD. The results showed that the surface substructure is refined during crystallization with shielding gas Ar. However, grains are seriously coarsened in the δ phase area. Widmanstatten γ and intragranular γ are formed as a result of δ ⟶ γ phase transition through the shear-diffusion mechanism. In the cooling process with shielding gas N2, the temperature range of each phase area narrowed obviously. Blocky γ began to appear because of the δ ⟶ γ phase transition through the diffusion mechanism. Generally, Ar and N2 have a strong effect only on the very shallow range from the surface. The area with a larger local misorientation with shielding gas Ar is at lath γ on the surface. With shielding gas N2, the large local misorientation area is the last contact position of γ during the δ ⟶ γ phase transition on the surface and cross section.